The diagnostic performance of mean neutrophil volume in neonatal sepsis: A systematic review and meta-analysis - Alpana Mishra; Pratap Kumar Jena; Santosh Kumar Panda (Pediatrics and Neonatology)
Background: There is a need for reliable diagnostic tests for early identification of sepsis to prevent neonatal mortality and antibiotic misuse. During sepsis, many immature neutrophils came into the bloodstream, altering the mean neutrophil volume (MNV) shown in the previous studies. Objectives: To summarize the diagnostic performance of mean neutrophil volume (MNV) in neonatal sepsis from the published literature. Method: Databases such as PubMed, Scopus, and Web of Science were searched from January 1990 to April 2023 for studies reporting MNV as a diagnostic test in neonatal sepsis. The pooled sensitivity, specificity, diagnostic odds ratio (DOR), and area under the curve (AUC) of the summary receiver operating characteristic (SROC) curve of MNV were estimated with reference blood culture-positive sepsis and clinical sepsis for meta-analysis. Result: The diagnostic performance of MNV was analyzed in 1685 neonates, including 829 septic and 856 non-septic neonates, from six prospective studies. The pooled sensitivity and specificity of MNV were 0.87 and 0.75, respectively, for neonatal sepsis; the DOR was 20.01 (95% CI: 5.90–67.82); and the AUC of the SROC for MNV was 0.81 (95% CI: 0.69–0.88). Higgins I2 was 92.1% (95% CI: 85.5%–95.7%). The diagnostic performance of MNV was better during sub-group analysis of studies reporting culture-positive sepsis (DOR 85.61). Conclusion: The diagnostic performance of MNV is moderate for neonatal sepsis. As the evidence originated from a small number of studies with marked heterogeneity, further large-scale diagnostic accuracy studies are recommended to resolve heterogeneity in the future.